2017
DOI: 10.1007/s13312-017-1183-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-autoimmune subclinical and overt hypothyroidism in idiopathic steroid-resistant nephrotic syndrome in children

Abstract: The prevalence of subclinical and overt hypothyroidism seems to be high in idiopathic SRNS, with almost one-third of children having overt or subclinical non-autoimmune hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
3
4
1
Order By: Relevance
“…. But persistently higher TSH was observed in atypically presented NS children which was similar to the findings of Dagan A et al and Marimuthu V et al in SRNS children 21,22 . TSH value was 6.92±2.9µIU/ml and 4.55±4.64 µIU/ml respectively.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…. But persistently higher TSH was observed in atypically presented NS children which was similar to the findings of Dagan A et al and Marimuthu V et al in SRNS children 21,22 . TSH value was 6.92±2.9µIU/ml and 4.55±4.64 µIU/ml respectively.…”
Section: Resultssupporting
confidence: 88%
“…In this study persistent subclinical hypothyroidism 4 weeks after steroid therapy was observed among 16.6% (4 were grade II and 3 were grade I) of atypically presented NS children. Sharma S et al, Kapoor K et al and Marimuthu V et al also observed subclinical hypothyroidism in SRNS children and the prevalence was 20%, 30% and 33.3% respectively 9,10,22 . But in this study only 14 atypically presented NS patients were steroid resistant.…”
Section: Resultsmentioning
confidence: 89%
“…15 Marimuthu V et al, conducted a cross-sectional study recruited 30 children (age 1-18 years) with idiopathic Steroid responsive nephrotic syndrome (SRNS) and 30 healthy controls. 16 To evaluate the frequency of nonautoimmune subclinical and overt hypothyroidism in children with idiopathic SRNS. Overt hypothyroidism was detected in 10 out of 30 children with idiopathic SRNS.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Saffari et al study underline the importance of conducting thyroid function tests in NS children with prolonged and severe urinary protein loss [ 4 ]. Almost one-third of children with idiopathic steroid resistant NS have overt or subclinical hypothyroidism [ 16 ]. Early diagnosis and treatment of thyroid hormone deficiency in children is critical for preserving normal linear growth and bone development [ 3 ].…”
Section: Discussionmentioning
confidence: 99%